(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article proposes to dig into collective creation processes in contemporary dance that invest in the city as a poetic, aesthetic and political matter based on the artistic production of Cia Damas em Trânsito e os Bucaneiros, a group from São Paulo, whose “compositional action” is based on improvisation and acting in urban spaces. Here, we point to the experience of creating the show Espaços Invisíveis (2013), in which the process was divided into a first moment of performative actions in the city of São Paulo, and a second moment, in which the material created on the street during the first phase inspired and originated the staging for unconventional space. Thus, we reflect on how corporeities, spaces and the city have been articulated in the craft of dance, to draw parallels between the collective process of the group and the ideas of “occupation dance”, relational and contextual art, dialoguing with discussions about the spatial and kinetic regimes in the cities according to Milton Santos and André Lepecki.